Workplace Rhythm Variability and Emotional Distress in Information Workers - Nepal, Subigya Kumar; Hernandez, Javier; Amores, Judith; Morshed, Mehrab Bin; Lewis, Robert; Prafullchandra, Hemma; Czerwinski, Mary (Extended Abstracts of the Conference on Human Factors in Computing Systems (CHI), 2023)
Regularity in daily activities has been linked to positive well-being outcomes, but previous studies have mainly focused on clinical populations and traditional daily activities such as sleep and exercise. This research extends prior work by examining the regularity of both self-reported and digital activities of 49 information workers in a 4-week naturalistic study. Our findings suggest that greater variability in self-reported mood, job demands, lunch time, and sleep quality may be associated with increased stress, anxiety, and depression. However, when it comes to digital activity-based measures, greater variability in rhythm is associated with reduced emotional distress. This study expands our understanding of workers and the potential insights that can be gained from analyzing technology interactions and well-being.